Innovations in Gender Equality and Women’s Empowerment: Understanding the Role of International Development Volunteers as Transnational Actors (Voluntaris - Zeitschrift für Freiwilligendienste und zivilgesellschaftliches Engagement , Sonderband, 2021)
Many studies have highlighted benefits of international volunteering, particularly the positive impacts for the volunteers themselves. Adding to this scholarship, the papers in the collection fill an important gap in our understanding of the impact of international development volunteering from the perspective of partner organization staff who work collaboratively with international development volunteers to promote gender equality and women’s empowerment. The collection provides insights into negotiated spaces and mutual learning as well as the unique role international development volunteers play as transnational actors by working closely with staff in development organizations. With contributions by Tiffany Laursen, Benjamin Lough, Tabitha Mirza, Rika Mpogazi, Lan Nguyen, Nnenna Okoli, Leva Rouhani, Khursheed Sadat, Somed Shahadu Bitamsimli, Pascale Saint-Denis und Rebecca Tiessen.